Attitudes of women in Scotland to contraception: a qualitative study to explore the acceptability of long-acting methods. Issue 4 (1st October 2008) - Glasier, Anna; Scorer, Jane; Bigrigg, Alison
Abstract : Background and methodology: Long-acting reversible contraception (LARC) (i.e. injections, implants and intrauterine methods) has the potential to reduce unintended pregnancies but in the UK these methods are under-used. To inform a campaign planned to increase awareness of LARC, eight focus discussion groups were held with 55 women in two cities in Scotland, UK. Trained interviewers sought spontaneous views of unintended pregnancy and contraception in general, and condoms and pills in particular, and attitudes towards health professionals giving contraceptive advice. Attitudes towards LARC were discussed both before and after women were given detailed information about the methods. Results: Women recognised the importance of using contraception but admitted to taking risks. Pills and condoms were familiar and acceptable despite undesirable side effects. Women were poorly informed about LARC, had firm but incorrect beliefs about their safety and side effects, disliked any method which involved an invasive procedure and/or vaginal examination, and had rather a low opinion of advice given by health professionals. Accurate information was not wholly successful in dispelling negative views of LARC. Discussion and conclusions: Many factors influence contraceptive choice. Attitudes towards methods are complex and may be difficult to change. Some barriers to LARC, including the need to see a health professional, cannot be overcome but giving more information about ease of use, reversibility, effects on weight and the positive experiences of other women, as well as describing these methods as lasting rather than long-acting, may help improve acceptability.